2021
DOI: 10.1136/bmjpo-2020-000930
|View full text |Cite
|
Sign up to set email alerts
|

ROP screening and treatment in four district-level special newborn care units in India: a cross-sectional study of screening and treatment rates

Abstract: ObjectiveBlindness from retinopathy of prematurity (ROP) in middle-income countries is generally due to absence of screening or inadequate screening. The objective of this study was to assess uptake of services in an ROP programme in four district-level special newborn care units in India.DesignCross-sectional study.SettingAll four neonatal units of a state in India where model programme for ROP had been introducedPatientsInfants eligible for screening and treatment of ROP between March and May 2017.Interventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…A secondary subanalysis was performed and found that there was a sex difference, with more male infants meeting the screening criteria for ROP than female infants (53% vs 47%). This is in contrast with previous data showing no sex differences among infants eligible for screening and those screened for ROP . In a recent large retrospective cohort study of 25 567 infants, Berrocal et al reported a high proportion of male patients (53%) screened for ROP, and this may reflect the higher percentage of male individuals requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
“…A secondary subanalysis was performed and found that there was a sex difference, with more male infants meeting the screening criteria for ROP than female infants (53% vs 47%). This is in contrast with previous data showing no sex differences among infants eligible for screening and those screened for ROP . In a recent large retrospective cohort study of 25 567 infants, Berrocal et al reported a high proportion of male patients (53%) screened for ROP, and this may reflect the higher percentage of male individuals requiring treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, the adoption of these guidelines in clinical practice across India has not been optimal. 33 , 34 …”
Section: Learning From Gpeimentioning
confidence: 99%
“…Despite the existence of established guidelines and standards for ACS administration, oxygen administration and saturation targeting, and screening for ROP, adherence to these guidelines by healthcare providers remains suboptimal. 34 , 59 Effective measures are required to promote adherence to established guidelines for ROP management. Focusing on addressing attitudinal barriers among healthcare providers can facilitate the uptake of best practices in ROP management, ultimately improving patient outcomes.…”
Section: Prevention Of Ropmentioning
confidence: 99%
“…Sabherwal et al . [ 6 ] reported ROP in only 11% of those screened in four district-level SNCUs. In this study, only 18% of the eligible infants got screened, whereas only 56.5% of them completed screening.…”
mentioning
confidence: 99%